Monitoring changes in proteome during stepwise adaptation of a MDCK cell line from adherence to growth in suspension. Issue 35 (20th August 2015) - Kluge, Sabine; Benndorf, Dirk; Genzel, Yvonne; Scharfenberg, Klaus; Rapp, Erdmann; Reichl, Udo
Abstract Adaptation of continuous cell lines to growth in suspension in a chemically defined medium has significant advantages for design and optimization in manufacturing of biologicals. In this work, changes in the protein expression level during a step-wise adaptation of an adherent Madin Darby canine kidney (MDCK) cell line to suspension growth were analyzed. Therefore, three cell line adaptations were performed independently. Two adaptations were monitored closely to characterize short term changes in protein expression levels after serum deprivation. In addition, initial stages of suspension growth were analyzed for both adaptations. The third adaptation involved MDCK suspension cells (MDCKSUS2) grown over an extended time period to achieve robust growth characteristics. Here, cells of the final stage of adaptation were compared with their parental cell line (MDCKADH). A combination of two dimensional differential gel electrophoresis for relative protein quantification and tandem mass spectrometry for protein identification enabled insights into cellular physiology. The two closely monitored cell line adaptations followed different routes regarding specific changes in protein expression but resulted in similar proteome profiles at the initial stages of suspension growth analyzed. Compared to the MDCKADH cells more than 90% of all changes in the protein expression level were identified after serum deprivation and were related to cytoskeletal structure, genetic information processing and cellular metabolism. Myosin proteins, involved in cellular detachment by actin-myosin contractile mechanisms were also differentially expressed. Interestingly, for both of the two adaptations, proteins linked for tumorigenicity, like lactoylglutathione lyase and sulfotransferase 1A1 were differentially expressed. In contrast, none of these proteins were differentially expressed for the MDCKSUS2 cell line. Overall, proteomic monitoring allowed identification of key proteins involved in adaptation from adherent to suspension growth. In addition, identified proteins related to tumorigenicity may represent markers to support cell clone selection at early stages of industrial cell line development.